2018
DOI: 10.15376/biores.13.1.1265-1277
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Prediction of Agarotetrol in Chinese Eaglewood Using Near Infrared Spectroscopy

Abstract: To overcome the numerous disadvantages of existing testing technology, a novel, fast, nondestructive, and quantitative technology for quality evaluation of Chinese eaglewood (CE) based on near-infrared (NIR) technology was proposed in this study. The extractives of CE were qualitatively analyzed to determine the types of volatile compounds using gas chromatography-mass spectroscopy and were quantitatively determined using high performance liquid chromatography (HPLC). Agarotetrol was quantitatively determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Later, investigators conducted further research and found that Chinese eaglewood extracts can regenerate impaired nerve cells, which exert compensatory effects. (Ding et al 2018).…”
Section: Chinese Eaglewood and Its Medicinal Valuementioning
confidence: 99%
“…Later, investigators conducted further research and found that Chinese eaglewood extracts can regenerate impaired nerve cells, which exert compensatory effects. (Ding et al 2018).…”
Section: Chinese Eaglewood and Its Medicinal Valuementioning
confidence: 99%